Fabrication of Ni-Mn Microprobe Structure with Low Internal Stress and High Hardness by Employing DC Electrodeposition - Kuan-Hui Cheng; Fu-Je Chen; Chun-Ying Lee; Chao-Sung Lin; Jung-Tang Huang; Chang-Cheng Lan; Ping-Huan Tsou; Tzu-I Ho (Advances in Materials Science and Engineering)
Due to its widely tunable mechanical property and incompatibility with most solders, Ni-Mn alloy can become a viable candidate in the fabrication of testing probe for microelectronic devices. In this study, the electrodeposition of Ni-Mn alloy in nickel sulphamate electrolyte with the addition of manganese sulphate was investigated under direct current (DC) power source. The effects of current density and Mn2+ concentration in the electrolyte on the coating composition, cathodic efficiency, microstructure and mechanical properties were explored. The results showed that the raise of the Mn2+ concentration in the electrolyte alone did not effectively increase the Mn content in the coating but reduce the cathodic efficiency. On the other hand, increasing the current density facilitated the codeposition of the Mn and rendered the crystallite from coarse columnar grain to the refined one. Thus, both hardness and internal stress of the coating increased. The fabrication of testing probes at 1 A/dm2 was shown to satisfy the high hardness, low internal stress, reasonable fatigue life, and nonsticking requirements for this microelectronic application.